(untitled) (Sustainability in Debate, 2015)
The article addresses the agriculture in the Federal District (DF) and the actions of the Technical Assistance and Rural Extension (ATER) in strengthening family farming towards an agro-ecological production. The National Policy for Technical Assistance and Rural Extension (PNATER), established in 2003, brings challenges to the services and institutions as it aims to contribute to sustainable rural development with the Agro-ecology as its guiding principle. Assuming that the family segment brings contributions to society as a whole, the Technical Assistance and Rural Extension Company (EMATER/DF) develops actions and encourages a more sustainable production for these farmers. The article presents an overview of agriculture in the Federal District, some considerations on family farmers and agro-ecological production. It also presents the actions of ATER in the development of family farming, reinforcing the need to expand and strengthen these services for sustainable development. The methodology used was literature review and analysis of secondary data obtained from government agencies.